Building the socialist legal state of Viet nam in the spirit of the National Congratulation, the 13th session of the Party - Dương Văn Đại (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
In a Document of the National Congress, the Communist Party of Viet nam identified one of the key missions: “Continuing to build and complete the socialist of law State of the People, by the People and the People led by the Communist Party of Viet nam is a central task for the reformationn of the political system”. Therefore, the affirmation and application of the Party is stand point in building the socialist rule of law State has profound theoretical and practical significance.